Perlindungan Hak Milik Warga Negara Indonesia dalam Perkawinan Campuran: Analisis Putusan Mahkamah Konstitusi Nomor 69/PUU-XIII/2015 - Ferdonictus Bernando Aloisius Sijabat; Muhammad Mikael Dirgantoro; Muhammad Azka Haidar Aslam (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This article analyzes Constitutional Court Decision Number 69/PUU-XIII/2015, which addressed the inconsistency between the community property regime under Law Number 1 of 1974 on Marriage and the nationality principle embodied in the Basic Agrarian Law. The case brought by Ike Farida, an Indonesian citizen married to a foreign national, revealed that the absence of a prenuptial agreement indirectly restricted her property ownership rights. Employing a normative juridical research method and a case approach, this study examines the Court’s legal reasoning, the ruling itself, and the conceptual implications of extending the validity of marital agreements to include postnuptial agreements within the Indonesian legal system. The decision is regarded as a progressive form of judge-made law while simultaneously highlighting the need for regulatory harmonization among family law, agrarian law, and private international law.